Preparation and in vitro transfection efficiency of chitosan microspheres containing plasmid DNA:poly(L-lysine) complexes - (:unkn) unknown (My University, 2003)
PURPOSE: Studies on DNA complexes with cationic polymers are prompted by the search for nonviral DNA carriers for gene therapy. Among them, poly(L-Lysine) (PLL) has been extensively studied. On the other hand, these systems deliver DNA as a bolus without long-term release. The aims of this study were to encapsulate plasmid DNA:poly(L-lysine) (pDNA:PLL) complexes into chitosan microspheres as an alternative to the PLL based gene delivery and investigate its in vitro release and transfection characteristics as well as plasmid DNA integrity and stability against serum and DNase I challenge. METHODS: pUC18 plasmid DNA that encoded beta-galactosidase was used as a model. The microspheres were prepared by complex coacervation method and the release and in vitro transfection properties were investigated. pDNA:PLL complexes were prepared at two different mass ratios. In vitro release studies were performed at 37 +/- 0.5 degrees C and drug release was monitored both spectrophotometrically and fluorometrically. Structural integrity of the pDNA:PLL complexes were determined by Southern blotting analysis. Protective effect of encapsulation of pDNA:PLL complexes against DNase I and serum treatment were also studied. In vitro transfection studies were performed by using 3T3 cell line. RESULTS: According to our in vitro release data, the mass ratio of pDNA:PLL significantly affected the release of pDNA:PLL complexes from chitosan microspheres, and the structure of the plasmid DNA did not change during the experiments. pDNA:PLL-loaded chitosan microspheres indicated high stability against fetal bovine serum and DNase I treatment for a week. In vitro transfection data showed that pDNA:PLL-loaded chitosan microspheres could be effectively transfected 3T3 cells in vitro. CONCLUSION: As a conclusion, pDNA:PLL complexes could be encapsulated into chitosan microspheres with maintaining their structural and functional integrity and this system may be a good alternative for polycation based gene carriers.
Keywords: Gene Transfer Techniques; Animals; DNA; Chitin; Chitosan; Microspheres; Mice; 3T3 Cells; Drug Carriers; Transfection; Drug Stability; Drug Delivery Systems; Plasmids; Genetic Therapy; Polylysine